Distribution, resources, features of biology, and the first results of specialized fishery of shrimp Pandalus goniurus in the Tatar Strait - Dmitry N. Yuriev; Andrey Yu. Povarov; Vladislav S. Lukjanov (Известия ТИНРО, 2016)
Shrimp Pandalus goniurus is poorly known in the Tatar Strait. Its distribution, state of stock, and features of biology are described on the data of 7 trawl surveys conducted by RV Buhoro in the western Tatar Strait in April-June 2009-2010 (227 trawls) and September-October 2011-2014 (589 trawls) and commercial catches obtained by fishing vessel Sovetskoye in May 2014 (50 trawls) and April 2015 (59 trawls). Horizontal opening of the scientific and commercial trawls was 16 and 35 m, respectively. About 14,000 individuals of the shrimp were subjected to biological analysis. P. goniurus was distributed along the whole continental coast of the strait northward from 47°20′ N and in spring concentrated at the depth from 50 to 120 m, rarely to 270-300 m, with single findings down to 340 m. Its stock fluctuated from 16 to 70 thousand t, on average 45,000 t (50-70 % within the territorial waters); possible annual catch was estimated as 5,000 t. Commercial fishery of this species was started in 2014 (mean CPUE 1.91 t/hour), the number of fishing vessels increased to 3 in 2015 (mean CPUE 3.26 t/hour, total landing 1160 t). The fishery is distinguished by easy hydroacoustic search of aggregations, long-time fishing within limited areas, high catches, including the catches in nighttime, and low bycatch. The highest concentration of P. goniurus was registered in April 2015: CPUE 11.86 t/hour, density 73.2 t/km2 or 10 ind./m2. Size-weight parameters of P. goniurus in the Tatar Strait were the best for all its populations: their average values in commercial catches in 2014/2015 were: carapace length 20.4/22.4 mm, individual weight 5.7/7.4 g or 165/116 ind./kg. Its larvae hatching was observed in April-May, mass post-hatching molt of females was supposedly in June-July and breeding molt and spawning - in September-October. First results of the fishery are analyzed, its prospects are estimated, and measures for its regulation are proposed.